2020
DOI: 10.22271/chemi.2020.v8.i4af.10059
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of biofertilizers and the combinations with chemical fertilizers on vegetative growth and yield of okra [Abelmoschus esculentus (L.) Moench]

Abstract: A field experiment was conducted during 2017 at Horticulture Research Farm-II, BBAU, Lucknow, Studies on the " Efficacy of biofertilizers and the combinations with chemical fertilizers on vegetative growth and yield of okra [Abelmoschus esculentus (L.) Moench]" revealed that vegetative attribute Plant height (136.00 cm),Number of Leaves/Plant(20.91),Diameter Stem of okra(2.32cm),Number of Days Taken To First Flowering(50.33),Number of Flower/Plant(20.33),Number Of Days Taken To First Fruit Formation(50.33), Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The results of the present study were in line with the findings of Choudhary et al [50]. The increment in the okra yield might be due to the growth-promoting abilities of the PGPR strains which were enhanced by their application in the form of organic carrier-based formulations [27,51].…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study were in line with the findings of Choudhary et al [50]. The increment in the okra yield might be due to the growth-promoting abilities of the PGPR strains which were enhanced by their application in the form of organic carrier-based formulations [27,51].…”
Section: Discussionsupporting
confidence: 92%
“…Muqtadir et al, (2019) found that, plant height of okra was significantly higher at 80 days after sowing from mixed of cow dung and inorganic fertilizer compared to other treatment. Kumar et al, (2019) reported that, combined application of organic and chemical fertilizers can increases plant height of okra. Hence, integrated nutrient management maintains organic matter in soil and improving nutrient and structural status of soils which influences vegetative growth and reproductive parameters of okra.…”
Section: Plant Height (Cm)mentioning
confidence: 99%
“…Van der Eijk et al reported that the high content of P under cultivated land (maize) than of grass land soils could be due to the continuous application of phosphorus fertilizer applications. Indiscriminate use of inorganic fertilizers leads to nutrient imbalance in soil causing ill effect on soil health and micro flora (Choudhary et al 2015).…”
Section: Soil Ph Ec and Ocmentioning
confidence: 99%